Mengenal Batik Paoman Indramayu Dan Sebagai Penggerak Daya Saing Ekonomi Lokal - Rinaldi, Oktavian (CV. Green Publisher Indonesia, 2025)
This research aims to analyze the marketing strategy of Indramayu Batik, especially Paoman Batik, as one of the creative economy products based on local culture that is facing challenges in the digital era. The main problems identified in this study include low digital literacy of MSME actors, limited product design innovation, and lack of optimal access to the wider market. The method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with batik artisans, business actors, and policy makers, as well as field documentation. The results of the study show that Batik Paoman actors apply a combined marketing strategy that includes conventional promotion through exhibitions, galleries, and local partners, as well as digital promotion through social media such as Instagram, Facebook, and e-commerce platforms. Other strategies include collaboration with local fashion designers, diversifying batik products into modern forms of fashion (ready to wear), and using cultural narratives (storytelling) as promotional attractions. Although these strategies are effective in expanding the market, business actors still face structural challenges, such as lack of continuous training, limited production capital, and lack of distribution support from the government. This research recommends the importance of synergy between batik actors, local governments, and MSME support institutions in building a sustainable and digital-based marketing system. This effort is also expected to strengthen the position of Indramayu Batik as part of a competitive cultural heritage at the national and global levels.